A ESPACIALIDADE EM BAIXO ESPLENDOR, ROMANCE DE MARÇAL AQUINO - George de Santana Mori (2023)
In contemporary times, the narrative space category and the theme that encompasses eroticism have been receiving a huge prominence in literary studies. Authors such as Bachelard (1978), Brandão (2013), Dalcastagnè and Azevedo (2015), Dimas (1985), Lins (1976), are important contributions that reflect on this category in current literary productions. However, the theme of Wester eroticism in not found among scholars of the spatial category, so it is necessary to understand it through research by authors such as Branco (1984), Bataille (2020), Bidarra (2006), Bulhões (2003), Freud (1990), and Maingueneau (2010). From this assumptions, as general objective, the spatial representation in Marçal Aquino narrative will be discussed in this research and, as specific objectives, the relationship of the spatial category with the eroticism will be investigated, as well as it contributions to the understanding of the senses, taking as research object the novel Baixo Esplendor (2021). To achieve the objectives described above, the general concepts of space, topoanalysis and other discussions such as ambiance, spatiality and in-between place will be presented to verify the way in which urban space is represented in Marçal Aquino´s narrative. Still, the contributions of psychoanalysis will be exposed to verify the intersection of eroticism that is presented in spaces through the characters. Also, associating the work and the theories, the way in which space and eroticism are related and contribute to the understanding of meanings in the novel will be analyzed. In the clipping used, it is possible to notice that Marçal Aquino highlights the eroticism permeating the entire narrative, presenting a literature with an infinity of subjectivities that resignify and reorient certain social spaces through the insertion and movement of his characters.